A meta-analytical review of the relationship between emotional intelligence and leaders' constructive conflict management. (January 2013) - Schlaerth, Andrea; Ensari, Nurcan; Christian, Julie
In this paper, we report the findings of a meta-analysis investigating the relationship between emotional intelligence (EI) and constructive conflict management, and the moderational role of leadership position and age. A total of 20 studies yielding 280 effect sizes and involving 5, 175 participants were examined. The results supported the hypothesis that EI is positively associated with constructive conflict management, and this relationship was stronger for subordinates than leaders. Contrary to our predictions, age was not a significant moderator. The limitations and implications are discussed in terms of psychometric issues, use of EI in leadership development and facilitation of problem solving, and for the further development of a constructive organizational culture.